Retrospective Analysis of a New Antigen Assay to Detect Anti-Transglutaminase Antibodies for Diagnosis and Monitoring of Celiac Disease. (May 2022) - Verbeke, Sandra; Canals, Andrea
BACKGROUND: The improved diagnosis and monitoring of celiac disease (CD) requires increasingly sensitive and specific serological markers. The development of new antigens ( neo-epitope s) able to detect different sets of anti-transglutaminase antibodies requires studies to demonstrate their advantages. OBJECTIVE: The goal of this study was to evaluate a new antigen for the detection of anti-tTG antibodies that combines tissue transglutaminase (tTG) and gliadin peptides. This protein complex occurs under physiological conditions in vivo at the time of deamination. PATIENTS AND METHODS: In this retrospective study, serum samples collected from patients from January to December 2018 were analyzed. Results of the determinations for neo-epitope anti-tTG antibodies (manufacturer's cut-off values: negative <12 U/mL, indeterminate 12-18 U/mL; positive >18 U/mL) were recorded along with age, sex, and duodenal biopsy results. Neo-epitope assay results were correlated with clinical and laboratory data and final CD diagnoses, using the manufacturer's cut-off value and a proposed alternate cut-off value. RESULTS: A total of 3820 neo-epitope anti-tTg determinations were analyzed. The percentage of values in the indeterminate zone was low (3.6%), with very few values (0.9%) at the exact manufacturer's cut-off limit (18 U/mL). This indicated a good resolution capacity for positives and negatives. The percentage of false positives was lower compared to a previous study (2013 study: 3.6%, vs current study (2018): 0.5%). A new positivity cut-off value was proposed: 20 U/mL, which increased the positive predictive value of the test. CONCLUSIONS: The neo-epitope assay is a more precise tool than recombinant human transglutaminase assay for the diagnosis and monitoring of celiac patients. It has a greater ability to resolve positive and negative results ("minimum indeterminate area"). Its greater sensitivity could detect situations (presentation and/or dietary transgression) where conventional techniques show negative or weakly positive serology.